Trabalho de campo como estratégia de ensino da geografia : identificando a aprendizagem significativa - Salles, Cristiano Ottoni Teatini (2016)
Regarding the constant changes of modern world, new readings related to teaching practices and strategies in basic education become necessary. Therefore, this paper assesses the use of fieldwork as an important methodological resource of Geography teaching-learning and the potentialities of this instrument in promoting Significant Learning. Supported by a reading of Humanist Geography and the Theory of Significant Learning, the fieldwork is studied as an instrument capable of awakening an inclination in learning from the students’ emotions and feelings inserted in the space and the occurrence of learning in a significant way in spaces of non-formal education, in the view of the formation of more critical and conscious citizens. Therefore, two fieldworks with high school students from the integrated technical course of IFES, Campus Linhares, ES were accomplished. Data collection were performed with the use of recording instruments of perceptions and experiences of students in field with pictures and texts and confrontation situations, problems, interviews and dialogues in a direct contact with other realities. The qualitative methodology of the Content Analysis was used for data analysis where conditions and evidences of Significant Learning were tried to be identified. Thus, it was possible to verify the fieldwork as effective in the development of a critical and investigative look and as a relevant procedure in the finding and production of students and teachers’ development in the promotion of Significant Learning, and the extension of its use in pedagogical practices of teaching regarded as important, mainly related to basic education.